2021
DOI: 10.1002/chem.202102700
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic Luminescence (MCL) of Purely Organic Two‐Component Dyes: Wide‐Range MCL over 300 nm and Two‐Step MCL by Charge‐Transfer Complexation

Abstract: Despite recent extensive studies on mechanochromic luminescence (MCL), rational control over the magnitude of the emission-wavelength shift in response to mechanical stimuli remains challenging. In the present study, a twocomponent donor-acceptor approach has been applied to create a variety of organic MCL composites that exhibit remarkable emission-wavelength switching. Dibenzofuranbased bis(1-pyrenylmethyl)diamine and typical organic fluorophores have been employed as donor and acceptor dyes, respectively. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…[17] The general mechanism of this typical two-step MFC materials is based on the transition of crystal-tocrystal during mild grinding, and followed by the transition of crystal-to-amorphous during sufficient grinding. [18] Unlike compound 4, there is no crystal-to-crystal transition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[17] The general mechanism of this typical two-step MFC materials is based on the transition of crystal-tocrystal during mild grinding, and followed by the transition of crystal-to-amorphous during sufficient grinding. [18] Unlike compound 4, there is no crystal-to-crystal transition.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports of stepwise MFC materials have referred to the crystalline dyes that exhibit continuous emission color changes after mild and sufficient grinding [17] . The general mechanism of this typical two‐step MFC materials is based on the transition of crystal‐to‐crystal during mild grinding, and followed by the transition of crystal‐to‐amorphous during sufficient grinding [18] . Unlike compound 4 , there is no crystal‐to‐crystal transition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports on the MLs showing large spectral shifts (4100 nm). [67][68][69][70][71][72][73][74][75][76] Zhu et al reported a benzothiadiazole based luminogen that exhibits a spectral shift of 160 nm on grinding. 77 Larger spectral shift results in high contrast mechanochromism and hence is useful for fabricating strain sensing devices.…”
Section: Rajneesh Misramentioning
confidence: 99%